Pengembangan Media Pembelajaran Video Interaktif dengan Aplikasi Inshot pada Mata Pelajaran PAI - Rizki Pebrina; Zeli Afrilia (IAIN Batusangkar, 2024)
The purpose of this research is to produce valid and practical interactive video learning media on ÔÇ£Akidah AkhlakÔÇØ subject using Inshot application by conducting ADDIE (Analysis, Design, Development, Implement and Evaluation) development model. The first stage was need analysis. Data were obtained by observing the teaching process of ÔÇ£Akidah Akhlak:, analyzing the media used by teachers, investigating studentsÔÇÖ characteristics, and examining the syllabus of ÔÇ£Akidah AkhlakÔÇØ subject for Grade X at MAN Solok. The second stage was design. The outline of the media program was drawn up at this stage. The third stage was development. At this stage, 3 experts validated the developed products. At the fourth stage (implement), a trial was carried out on grade X students of MAN in Solok. At the last stage (evaluation), the validity and practicality of the product were examined. Based on the data analysis, the validity of the product was 0.89 in highly valid category and the practicality was 0.86 in highly valid category. It can be concluded that the interactive video learning media using Inshot application can be used in ÔÇ£Akidah AkhlakÔÇØ learning process.